Australian Medical/Health Journalists on the Value of Science-based Education and Training. (December 2016) - Furlan, Patrizia
One of the criticisms of medical/health news is that it sensationalizes or miscommunicates research rather than accurately inform the public. A mixed methods study of Australian medical/health reporters and their public relations sources found that while many journalists recognize the need for extra training for those without any science background in order to better interpret and report medical research, others consider journalism education sufficient. While the majority considered science-based training necessary, there was little consensus on what form this should take. Suggestions ranged widely from weekend workshops to training in medical/health reporting at universities. Others considered practising 'good' journalism and experience in the field as all that is required.